(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article discusses the different approaches to the discourse of modern civil society, the priority is determined by its values of measurement. As the supporting structures are allocated free nature of association and dependence of the state from society; solidarity, a sense of responsibility, the development of social capital; statement as a value – a culture of peace and dialogue; independent livelihoods of citizens, a steady middle class; developed a feedback system: the independence of the public sphere, officials are accountable to society; formation mechanisms of public authorities. We present a statistical analysis of the development of NGOs in Kazakhstan, the areas of activity and attitude to it by society. Attempts to conceptualizing factors and causes of the current state of civil society in Kazakhstan. The main obstacles to the development of active civil relations, settle historical, influenced the mentality and psychology of the relationship of government and society, formal and legal, economically stimulating the activation of civil society institutions, and others. Substantiates that the development of the civil initiative is a prerequisite and basic design civil society, which form in the citizens a sense of responsibility, moral usefulness and organic solidarity. Key words: civil society, democracy, legitimacy, organic and mechanical solidarity, social capital.